A phenomenological approach to virtual reality in psychiatry education - Pedersen, Kamilla; Musaeus, Peter (Frontiers in Virtual Reality, 2023)
The idea of using virtual reality for educational purposes has been present since the inception of the virtual reality era (Makhkamova et al., 2019). Over the past two decades, virtual reality has firmly established itself as a prominent training technology in medical education, finding prominence in the fields of medicine, surgery and psychiatry education. In the realm of psychiatry education, virtual reality remains relatively new and unexplored. Medical education's use of virtual reality encompasses diverse designs, with various formats, applications, and focuses depending on the target audience and clinical context. These formats include text descriptions, video materials, simulated patients, and computer-based multimedia. Some patient cases emphasize theory to impart knowledge about diseases and treatments, while others take a practical approach, emphasizing skill development in communication, teamwork, and decision-making (Pomata, 2014). Training technologies in surgery and medicine often target specific practice domains, concentrating on procedural skills and transferring cognitive knowledge (Courteille, 2008;Cheung et al., 2018). One such example is serious gaming, utilizing game technology to recreate work and decision-making scenarios, providing an immersive environment for interactive clinical learning (Lam et al., 2019). A crucial element in serious gaming depends on interactions where learners can engage with the physical layout of the ward, manipulate medical equipment, and have the freedom to make choices and respond to a wide range of interactions with virtual patients and healthcare professionals (Kampa, A. Burelli, P. Haake, 2016). These virtual environments are meticulously crafted to replicate real-world hospital settings, offering learners a realistic training experience with varying levels of interactivity and graphics (Graafland, Schraagen and Schijven, 2012).